2005
DOI: 10.1002/anie.200462515
|View full text |Cite
|
Sign up to set email alerts
|

Metal@MOF: Loading of Highly Porous Coordination Polymers Host Lattices by Metal Organic Chemical Vapor Deposition

Abstract: Standing out from the vast majority of metal organic coordination polymers is the class of highly porous basic zinc carboxylates developed by Yaghi and co-workers.[1] Its prototype is MOF-5 (MOF = metal organic framework), in which {Zn 4 O} building blocks are linked together by terephthalate bridges to form a zeolite-like, cubic framework.[2] The extremely high specific surface area [2] of up to 4500 m 2 g À1 and a pore volume of 0.69 cm 3 cm À3 (for MOF-177), which has not been surpassed by any other crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
444
1
10

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 683 publications
(468 citation statements)
references
References 36 publications
13
444
1
10
Order By: Relevance
“…A maioria dos trabalhos recém publicados é referente ao emprego de metais de transição na construção de redes de coordenação, [10][11][12] enquanto os sistemas com lantanídeos são muito menos estudados. [12][13][14] Os lantanídeos possuem propriedades espectroscópicas peculiares, como tempo de vida longo e bandas de emissão finas e bem definidas.…”
Section: Introductionunclassified
“…A maioria dos trabalhos recém publicados é referente ao emprego de metais de transição na construção de redes de coordenação, [10][11][12] enquanto os sistemas com lantanídeos são muito menos estudados. [12][13][14] Os lantanídeos possuem propriedades espectroscópicas peculiares, como tempo de vida longo e bandas de emissão finas e bem definidas.…”
Section: Introductionunclassified
“…157 The clustering of transition metals in MOFs was also experimentally proven. 161,162 This clustering of exposed metal atoms could be prevented by using another organic linker such as [(Bipydc)M(CO) 4 ] 2À (Bipydc = 2,2 0 -bipyridine-5,5 0 -dicarboxylate) which is shown in Fig. 9(a).…”
mentioning
confidence: 99%
“…It is worth noting that Au clusters supported on Al-MIL53 could promote the one-pot N-alkylation of 4 with 5 under inert atmosphere without O 2 and H 2 to produce 7 in the co-presence of base (entry 5), whereas Au NPs on CPL-2 and on MOF-5 could not (entry 7,8). It can be assumed that hydrogen atoms generated by the dehydrogenation of 4 are used for the hydrogenation of 6 to give 7.…”
Section: One-pot Synthesis Of Asymmetric Secondarymentioning
confidence: 99%
“…Porous coordination polymers (PCPs) with highly ordered nanometer-sized porous structures have been attracting growing interests as supports for metal clusters smaller than 2 nm in diameter (7)(8)(9)(10)(11). It has been reported that Pd (7,8), Cu (7), Ru (9) clusters in the range of 1-3 nm could be deposited on or in PCPs by chemical vapor deposition (CVD) whereas Au clusters with diameters of smaller than 2 nm had been hardly obtained by CVD because of the weak interactions of Au with PCP frameworks (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation